2020
DOI: 10.1007/s42452-020-03890-w
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk assessment of heavy metal contamination in mangrove forest sediment of Gulf of Khambhat region, West Coast of India

Abstract: Mangrove forests are in severe threat from heavy metals pollution stimulated by the several human activities connected with hasty industrialization and urbanization. Heavy metals contamination of mangrove ecosystems has caused serious concern worldwide. The objective of the present research is to identify the heavy metal pollution in the mangrove forest sediments of the Gulf of Khambhat, Gujarat, India. The samples were collected from the 12 selected sites of the GoK and investigated for Pb, Cu, Cd, Cr, Ni, As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Based on Igeo value, it can be concluded that the studied area enriched with As, Cd, Mo, and Hg. The presence of various metals in sediment may result from the interaction of elevated particulate matter with relatively unpolluted sediments (Singh et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Based on Igeo value, it can be concluded that the studied area enriched with As, Cd, Mo, and Hg. The presence of various metals in sediment may result from the interaction of elevated particulate matter with relatively unpolluted sediments (Singh et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The pollution load index is used to determine the quality of pollution. The pollution load index value uses the formula (Shaheen et al 2019;Singh et al 2020). The formula of Pollution Load Index (PLI) = [Cf1 x Cf2 x Cf3….…”
Section: Pollution Load Index (Pli)mentioning
confidence: 99%
“…One of leading concern of heavy metal toxicity is its impact on fish, which are not only a key component of many ecosystems, but also a significant dietary source for various top consumers, including humans 1,2 . Rapid development in the industrial, agricultural, and domestic sectors, coupled with the imperative to meet the needs of a rapidly growing world population, has led to an increase in a variety of pollutants in recent decades 3,4 . Among these, the proliferation of carcinogenic heavy metals such as cadmium (Cd), lead (Pb), zinc (Zn), chromium (Cr), mercury (Hg), and others has become a rising concern.…”
Section: Introductionmentioning
confidence: 99%